Identifying ‘corridors of HIV transmission’ in a severely affected rural South African population: a case for a shift toward targeted prevention strategies - Tanser, Frank; Bärnighausen, Till (International journal of epidemiology, 2018)
AbstractBackground. In the context of a severe generalized African HIV epidemic, the value of geographically targeted prevention interventions has only recentl